Analisis Ekonomi Sistem Fertigasi Pada Budidaya Bawang Merah (Allium cepa L.) - Novianti, Evita; Tusi, Ahmad; Amien, Elhamida Rezkia; Suharyatun, Siti (abe.fp.unila.ac.id, 2024)
Shallot cultivation using the fertigation system is a method of providing fertilizer and irrigation water for shallot plants through a drip irrigation system, which is more efficient and effective, so as to increase productivity. However, farmers still do not know information regarding the implementation of the fertigation system on shallots and the benefits. The purpose of this study was to analyze the cost requirements of the fertigation system, the economic feasibility of the business, and the minimum area of shallot cultivation area for business farmers who use the fertigation system and do not apply the fertigation system in Nambahrejo Village, Kota Gajah District, Central Lampung. There are two types of data obtained, namely primary data obtained from direct survey methods or collecting questionnaire data and interviews with farmers, and secondary data from literature and the like. The research results show that the shallot fertigation system with a quarter ha land area is feasible with a total cost value of ±Rp. 134,044,026,-/year, the NPV value is Rp. 291,029,252/year, Net B/C of 1.25, IRR of 35%, and payback period (PP) of 0.58 years / ±7 months. Shallot cultivation is recommended to be carried out with a minimum area of ¼ ha with 3 planting periods per year.